PENGARUH SOFT SKILL DAN HARD SKILL MAHASISWA TERHADAP KESIAPAN KERJA DI ERA REVOLUSI INDUSTRI 4.0 - Telaumbanua, Aprianus; Telaumbanua, Arisman (Jurnal Suluh Pendidikan, 2024)
This study explores the influence of soft skills and hard skills of students in the Building Engineering Education Program on job readiness in the era of the Industrial Revolution 4.0. In an increasingly competitive job market, technical abilities (hard skills) and interpersonal skills (soft skills) are keys to success. Hard skills encompass technical abilities acquired through formal education, while soft skills involve interpersonal abilities, communication, and time management. This research employs a quantitative approach with multiple linear regression analysis to measure the impact of both types of skills on students' job readiness. Data were collected through questionnaires from final semester students of the Building Engineering Education Program at Nias University. The analysis results indicate that both soft skills and hard skills positively and significantly influence students' job readiness. These findings underscore the importance of integrating soft skills and hard skills in preparing students to meet the demands of the digital era job market.